Review of Lightweight Vibration Isolation Technologies for Marine Power Devices - Yuanran Qiu; Wei Xu; Zechao Hu; Junqiang Fu; Mengxuan He (Shock and Vibration)
Vibration induced by marine power devices (MPD) transmitting to the hull structure is one of the most important factors that cause ship vibration and underwater sound radiation. Vibration isolation technologies (VIT) are widely applied to reduce the vibration transmission. However, the overweight issue of VIT for marine power devices is a currently challenging engineering problem. The current reserve of lightweight and high-efficiency VIT for MPD and relevant theoretical and design research are seriously insufficient. This article first elaborates the causes of the overweight problem of VIT for MPD: (1) failing to grasp the quantitative law; (2) single vibration suppression mechanism. Then, it systematically sorts out the technical methods and application examples with potential to solve the overweight problem, such as dynamic optimization design, lightweight material method, novel intermediate mass structures, distributed dynamic vibration absorbers (DDVAs), locally resonant structures (LRS), particle damping (PD), quasizero stiffness isolators (QZSI), and active vibration control (AVC) technologies. Finally, the future development of lightweight VIT for MPD is prospected. It can be used as a reference for marine vessel vibration attenuation research and engineering design.